Fala, Vitória! : a variação do imperativo na cidade de Vitória/ES e sua posição no cenário nacional - Evangelista, Elaine Meireles (2010)
This paper analyses the alternation in grammatical imperative mood use under the light of Labovian Sociolinguistics in the city of Vitória/ES, on what concerns forms contemporaneously associated with the indicative mode (speak/look/let/say) or with the subjunctive mode (speak/look/let/say) in affirmative and negative statements both in speech and writing in the exclusive context of the pronoun you. Four corpora were used, namely: (1) interviews from the project “The Portuguese Spoken in the City of Vitória - PortVIX”, Federal University of Espírito Santo – interviews labovian; (2) ads, and column headlines in two local newspapers, A Tribuna and A Gazeta – written in non-dialogue form; (3) comic strips from Marly, the spinster, a local character created by cartoonist and writer Milson Herinques over 30 years ago – written in dialogue format; and (4) television media speech in two local TV broadcasts, Full Account and Tribuna News. Such corpora gave us a wider view of the tendencies already noticed in other investigations about variation and change of the imperative mood in Brazilian Portuguese. The studies of imperative mood variation in some Brazilian localities indicate a distance between the Grammar rule and the use of the imperative mood, remarking that such variation points towards a linguistic change considering that, unlike the register of grammatical tradition, imperative mood forms associated with the indicative mode (speak/look/let/give/come) occur widely in a context of the use of the pronoun you. The main object of this study is to verify the alignment of the imperative mood use in the city of Vitória in the national context, since there is a lack of sociolinguistic studies in the state of Espírito Santo; and also to contribute towards mapping imperative mood use in Brazil. In oral language, our results amounting to 97% of imperative mood use associated with the indicative mode, confirm the geographical clipping of capital cities, as they come close to those found in the oral language of capital cities in the Center-West, Southeast, and South regions, which show percentiles above 90 and are far from the results of the Northeast region capitals, especially Salvador – the capital of Bahia – which boasts a global 28% of imperative mood use associated with the indicative mode. The results of all the analyzed corpora have revealed and confirmed some trends, such as the strong restriction of pre-verbal negation to imperative mood use associated with the indicative mode; and the role of the number of syllables of the verb in the infinitive, the role of the presence, type and position of pronouns, and the role of discourse markers, for the understanding of such a variable phenomenon. In non-dialogue format writing, in special, results confirmed that discourse anchors tend to also favor the use of imperative clauses associated with the indicative mode and that, in such type of writing, there is a great promotion of imperative mood use in the subjunctive form. Television media data have revealed the importance of the presence of dialogue in communicative, in which speech is more planned, towards the favoring of imperative mood associated with indicative mode. In short, our investigation has confirmed some regularity if compared to other studies, which indicates some trends that help explain imperative mood variation.